Strategies to Prevent Preterm Birth - Newnham, John P.; Dickinson, Jan E.; Hart, Roger J.; Pennell, Craig E.; Arrese, Catherine A.; Keelan, Jeffrey A. (Frontiers in Immunology, 2014)
After several decades of research we now have evidence that at least six interventions are suitable for immediate use in contemporary clinical practice within high-resource settings and can be expected to safely reduce the rate of preterm birth. These interventions involve strategies to prevent non-medically indicated late preterm birth; use of maternal progesterone supplementation; surgical closure of the cervix with cerclage; prevention of exposure of pregnant women to cigarette smoke; judicious use of fertility treatments; and dedicated preterm birth prevention clinics. Quantification of the extent of success is difficult to predict and will be dependent on other clinical, cultural, societal and economic factors operating in each environment. Further success can be anticipated in the coming years as other research discoveries are translated into clinical practice, including new approaches to treating intra-uterine infection, improvements in maternal nutrition and lifestyle modifications to ameliorate maternal stress. The widespread use of human papillomavirus (HPV) vaccination in girls and young women will decrease the need for surgical interventions on the cervix and can be expected to further reduce the risk of early birth. Together, this array of clinical interventions, each based on a substantial body of evidence, is likely to reduce rates of preterm birth and prevent death and disability in large numbers of children. The process begins with an acceptance that early birth is not an inevitable and natural feature of human reproduction. Preventative strategies are now available and need to be applied. The best outcomes may come from developing integrated strategies designed specifically for each health care environment.